Low Binder Concrete and Mortars - de Brito, Jorge; Kurda, Rawaz (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This book is the result of a Special Issue published in Applied Sciences entitled "Low Binder Concrete and Mortars". The main aim of this work is to highlight practical approaches that facilitate the production of low binder content concrete and mortar with an acceptable level of technical performance (e.g., mechanical and durability) and environmental impacts (e.g., ecotoxicological and global warming). Its contents are organized in the following sections: Developing Zero-Cement Binder; Ecotoxicological and Chemical Characteristics of the Non-conventional Materials Used to Replace Cement and Natural Aggregates; Reduce the Environmental Impacts and Resources Use of Binders; Modify the Characteristics of the Cement-Based Materials; Low Binder Concrete On-Site Application; Sustainable Cement-Based Materials in Road Engineering.